2021
DOI: 10.14505/jemt.v12.1(49).09
|View full text |Cite
|
Sign up to set email alerts
|

Hotel Guests’ Perceptions of Environmentally Friendly Practices in Jordan

Abstract: Tourism still generates negative effects on the environment that consequently objected the green practices in hotels; therefore, this study comes to measure the perception of international guests towards green practices in the Jordanian hotels. This study considers the first attempt that linked the tourists' perceptions toward green practices in hotels and their willingness to stay in eco-label hotels in Jordan. The study relied on the quantitative approach to measure the level of those practices as 270 questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…For instance, an empirical investigation conducted by Hou and Wu [ 16 ] revealed that tourists’ intention of staying in green hotels is significantly influenced by the level of their awareness and perceptions of green building design attributes. In the Jordanian green hotel context, a positive but moderate correlation has been found between tourists’ perceptions of environmental practices and their stay in eco-hotels [ 51 ]. A relevant study explored the influence of consumers’ environmental awareness on their intention to visit green hotels in north Cyprus, and found that environmental awareness and concern directly and positively influenced the guests’ intentions to visit hotels [ 52 ].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…For instance, an empirical investigation conducted by Hou and Wu [ 16 ] revealed that tourists’ intention of staying in green hotels is significantly influenced by the level of their awareness and perceptions of green building design attributes. In the Jordanian green hotel context, a positive but moderate correlation has been found between tourists’ perceptions of environmental practices and their stay in eco-hotels [ 51 ]. A relevant study explored the influence of consumers’ environmental awareness on their intention to visit green hotels in north Cyprus, and found that environmental awareness and concern directly and positively influenced the guests’ intentions to visit hotels [ 52 ].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The results indicated that when consumers choose hotels for accommodations, green hotels will not be listed as a factor in purchasing decisions. Consumer consider price and only have economic motivation [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the options offered, respondents could also choose the "other" option and express their own opinion or position on the issue. An important question was whether the hotel had an environmental management concept (Tourkolias et al 2020;Rawashdeh and Al-Ababneh 2021). The questionnaire also asked whether the hotels considered implementing environmental management as an advantage and whether they would seek to obtain an environmental management certificate.…”
Section: Methodsmentioning
confidence: 99%